The Concept of Color In Batak Mandailing Communities: Natural Semantic Metalanguage Approach - Dina Amalia; Mulyadi Mulyadi (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2022)
The concept of naming colors in each culture and language is certainly different. Color is defined as a means of expression to interpret the meaning exactly. This study was analyzed about the concept of color in the Batak Mandailing culture. The aim of the study is to describe the vocabulary of colors and their meanings in the Batak Mandailing language. The theory used in this study is the theory of Natural Semantic Metalanguage (NSM). The type of method used in this study is descriptive qualitative. The technique used is the recording and note-taking technique and to obtain the data it is done by recording the use of language, both written and spoken language. Data were collected through primary and secondary sources. Where the primary source collects library data about the names of colors. Then, secondary data was taken by conducting interviews with native speakers of the Batak Mandailing language. The results of this study indicate that there are six basic colors in the Batak Mandailing language, namely lomlom, bontar, rara, gorsing, average for green and average for blue. And the color pattern of the Batak Mandailiing language is formed by the components 'X is something' and 'X is something like this'